Design of a Finger-Sized Voice Coil Motor for High-Speed Scanners - Kang, Sunghoon; Jeong, Yong Gon; Choi, Young Man (International Journal of Precision Engineering and Manufacturing, 2023)
Voice coil motor (VCM) is a versatile high-precision actuator for miniaturization of electronic devices such as auto-focusing unit for cell-phone cameras and pickup actuators in hard disk drives. VCM can be also applied to hand-held medical devices in a slender and cylindrical shape. For a miniaturized design, of which size is comparable to human finger, it is crucial to make thrust force uniform over its moving range and power optimized. In this study, we propose a miniaturized cylindrical VCM with symmetric stator. The symmetric arrangement has advantages of enhancing uniformity of magnetic flux density in the air gap and reducing leakage flux due to its closed form. However, leakage flux between yokes inside the actuator still affects the thrust force, which is critical for a miniaturized design. Considering this leakage flux, a magnetic equivalent circuit model of the VCM is developed and verified by comparing with finite element analysis. We optimized the proposed VCM to maximize the slenderness for miniaturization with a stroke of 10 mm. Fabricated VCM was of 13 mm diameter and 40 mm length. Measured magnetic flux density and force constant are well matched with the model prediction. Finally, we built a high-speed linear scanner to verify the performance of the VCM. For a 10-Hz sinusoidal trajectory, the tracking error was less than ± 35 μm in RMS value. During full-stroke scanning, the temperature of coil was maintained at 34.5 °C.
Keywords: High Speed; High-precision; Leakage flux; Magnetic equivalent circuits; Magnetic leakage flux; Miniaturisation; Permeance method; Symmetrics; Thrust forces; Voice coil motors; Magnetic equivalent circuit; Magnetic leakage flux; Permeance method; Voice coil motor